2021
DOI: 10.1097/nmd.0000000000001400
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and Hope Among Yazidi Women Released From ISIS Enslavement

Abstract: This study aimed to explore the levels of resilience and hope among Yazidi women who survived captivity by Islamic State of Iraq and Syria (ISIS) and to examine its relationship with posttraumatic stress disorder (PTSD), generalized anxiety, and depressive symptoms. In this cross-sectional study, 139 formerly enslaved Yazidi women were assessed. The mean scores of resilience and hope were below the suggested cutoff means (M = 2.47, SD = 0.48, R = 1-5) and (M = 31.6, SD = 11.7, R = 8-64), respectively. Sociodem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Karim et al, found being female, of younger age, holding an academic degree and (contrary to the current study) being a college student were associated with more prominent degrees of anxiety 9. Taha et al, also reported type of employment as an important sociodemographic factor influencing knowledge, attitude and behaviors toward COVID-19 amongst the northern Iraqi population 15 . Participants in this study reported important and statistically significant increase in bad mood and feelings during the confinement period.…”
Section: Discussionmentioning
confidence: 97%
“…Karim et al, found being female, of younger age, holding an academic degree and (contrary to the current study) being a college student were associated with more prominent degrees of anxiety 9. Taha et al, also reported type of employment as an important sociodemographic factor influencing knowledge, attitude and behaviors toward COVID-19 amongst the northern Iraqi population 15 . Participants in this study reported important and statistically significant increase in bad mood and feelings during the confinement period.…”
Section: Discussionmentioning
confidence: 97%